DIGITAL PLACEMAKING FOR BORDERLESS HERITAGE: INTERACTIVE NARRATIVES IN SURABAYA’S HISTORICAL IDENTITY - Noer, Noer Sidik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the role of digital placemaking and interactive narratives in strengthening Surabaya's historical identity as a heritage tourism destination in the digital era, while also identifying the challenges and opportunities involved in its development. Method: Employing a qualitative case study approach, the research focuses on the digitalization of Surabaya’s historical identity. Data were collected through in-depth interviews with relevant stakeholders, participant observation, and document analysis of heritage tourism policies. Thematic analysis was used to uncover patterns related to digital placemaking, stakeholder collaboration, and narrative effectiveness. Results: The findings reveal that Surabaya has initiated several technology-driven heritage tourism projects utilizing AR, VR, and interactive storytelling. However, challenges remain in the form of limited narrative authenticity, fragmented stakeholder coordination, and uneven technological adoption. Novelty: This study contributes by highlighting the strategic potential of digital placemaking and immersive narratives in enhancing urban historical identity and tourism engagement, offering a framework for collaborative and sustainable digital transformation in heritage tourism.